Hubungan Status Sosial Ekonomi dengan Kejadian Stunting pada Balita Usia 12-60 Bulan Di Puskesmas Kaliwates - Yuningsih, Yuningsih; Sari, Asri Iman; Handayani, Yuni (Puslitbang Sinergis Asa Professional, 2023)
Stunting is a condition of impaired growth and development in children that can result in morbidity, mortality, and motor development impairment. The occurrence of stunting is often associated with malnutrition. Jember is a regency with the highest prevalence of stunting in East Java in 2020. Socioeconomic status, such as parental education level and occupation, can influence access to adequate nutrition and healthcare, which in turn contribute to the risk of stunting. The objective of this study was to determine the relationship between socioeconomic status and the occurrence of stunting among children aged 12-60 months in Kaliwates Community Health Center. This study employed a quantitative approach with an analytical observational design and a cross-sectional study design. The study population consisted of 580 children. The sampling technique used in this study was Proportionate Stratified Random Sampling, calculated using the Issac and Michael formula, resulting in a sample of 58 respondents who met the inclusion criteria. The data were analyzed using univariate and bivariate analyses with statistical tests using Chi-Square. The Chi-Square test results indicated a significant relationship between fathers' occupation (p = 0.003), mothers' occupation (p = 0.000), fathers' education (p = 0.001), mothers' education (p = 0.000), and the occurrence of stunting among children aged 12-60 months in Kaliwates Community Health Center. To prevent and address the occurrence of stunting among children in Kaliwates Community Health Center, it is important to provide balanced nutrition education, improve access to nutritious food, regularly monitor children's growth and development, involve the community, strengthen parental roles, and conduct regular program monitoring and evaluation.